DESIGN OF DRAINAGE SYSTEM AND WATER SUPPLY OF KIARACONDONG MARKET BUILDING - Martomu David, Rainhart
The existence of traditional markets has received less attention from the government which makes the handling not optimal. The physical condition and management problems have not been dealt well. The design of the Kiaracondong Market in Bandung City is carried out to improve traditional market as a place to fulfill community needs. This includes rebuilding the Kiaracondong Market, adding other facilities and functions within the land to maximize land use, as well as providing additional facilities that can subsidize market fees. The design of water resources includes drainage network design and the application of a rainwater harvesting (RWH) system to meet the demand for clean water. The drainage network is designed to ensure that the market and its surroundings do not flood due to rainwater. The drainage network is designed with a zero delta Q system to ensure the market does not add to the runoff of the Cicadas River. The zero delta Q concept is implemented by utilizing a rainwater utilization system as a source of freshwater for the market. The design of water resources in this final project begins with hydrological analysis and flood analysis. The selected rainfall observation station is the Stasiun Geofisika Bandung with an observation period of 20 years. Frequency analysis was carried out using the normal method, the lognormal method, the log pearson type III method, and the Gumbel method. Hydrographic analysis was used using the Snyder method, Nakayasu method, ITB 1 method, and ITB 2 method. Flood analysis was carried out using the HEC-RAS software. The scope of the drainage network design is based on rainwater. The water runoff analysed came from the roof and ground floor surface of the market. The drainage design is carried out by considering the building design and land use of the market building. The dimensions of the drainage network components are designed. The results of rain runoff are used to ensure the zero delta Q principle is applied to the drainage network. The supply of clean water for the market is sourced from PDAM and rainwater harvesting. Market clean water needs are analysed and then compared with the analysis results of rainwater availability. Availability of rainwater determines the capacity of the water storage used. The designed water reservoirs are ground water tanks (GWT) and roof water tanks (RWT). Clean water distribution components are designed in the form of pumps and pipes. Pumps and pipes delivers water from GWT to RWT and RWT to the rest of the building.